Perbandingan Kinerja Algoritma Fibonacci Retracement dalam Prediksi Pergerakan Harga Saham - Ulung Wira Yuda; Ahmad Juan Syahwali; Tata Sutabri (Jurnal Manajemen Informatika & Teknologi, 2025)
This study explicitly examines the performance of the Fibonacci Retracement algorithm in predicting the direction of stock price movements and compares it with other technical indicators, namely Moving Average (MA) and Relative Strength Index (RSI). Fibonacci Retracement is used to identify potential support and resistance levels based on certain mathematical ratios. The data used are historical stock prices of five financial sector companies listed on the Indonesia Stock Exchange (IDX) during the period 2020 to 2024. The evaluation process is carried out by measuring the level of accuracy of trend direction predictions and the performance of the applied trading strategies. The results of the analysis show that the use of Fibonacci Retracement separately has limitations in determining trend direction. However, when combined with MA and RSI, its predictive ability increases significantly, resulting in a more consistent trading strategy